Enhancement of catalytic activity by addition of chlorine in chemical vapor deposition growth of carbon nanotube forests. (30th August 2022) - Kinoshita, Toshiya; Karita, Motoyuki; Chikyu, Norikazu; Nakano, Takayuki; Inoue, Yoku
Abstract: In carbon nanotube (CNT) growth, the role of catalytic nanoparticles involves complex processes of feedstock gas decomposition, carbon feedstock transport, and CNT crystal precipitation. We report on the improvement of the catalytic activity by chlorine addition during the CNT forest growth process. The addition of Cl2 enhanced the diffusion rate of carbon in the catalysts, and thus changed the rate-limiting step from iron diffusion in the catalyst to the feedstock gas decomposition on the catalyst surface, leading to a higher growth rate and longer catalyst lifetime. The addition of Cl2 directly affected numerous CNT structural parameters, including the CNT diameter, number of walls, and crystal quality. Furthermore, the Cl2 addition made the CNT forest super-aligned, and it enhanced the dry spin capability of the CNT forests, allowing CNT webs to be continuously drawn from the forests. Graphical abstract: Image 1